1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 525 (1809) - (:unkn) unknown (My University, 1659)
"That every man able to beare armes have in his house a fixt gunn two pounds of powder and eight pound of shott at least"
Keywords: REQUIRED POSSESSION